2016
DOI: 10.1093/nar/gkw055
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomics elucidates adaptive phenol tolerance and utilization in lipid-accumulatingRhodococcus opacusPD630

Abstract: Lignin-derived (e.g. phenolic) compounds can compromise the bioconversion of lignocellulosic biomass to fuels and chemicals due to their toxicity and recalcitrance. The lipid-accumulating bacterium Rhodococcus opacus PD630 has recently emerged as a promising microbial host for lignocellulose conversion to value-added products due to its natural ability to tolerate and utilize phenolics. To gain a better understanding of its phenolic tolerance and utilization mechanisms, we adaptively evolved R. opacus over 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 91 publications
0
93
0
Order By: Relevance
“…However, the energy consumption, high cost, hazardous byproducts production, and poor efficiency of these methods limited their widespread applications (Banerjee and Ghoshal, 2011). The natural ability of microorganisms to degrade phenol, and a few biological treatments of phenol are explored and found to be more efficient than physicochemical methods (Jiang et al, 2005;Banerjee and Ghoshal, 2011;Yoneda et al, 2016). It is a challenge for the wide applications of biological methods that these compounds are toxic to microbial cells, can prolong the lag phase, and reduce the phenol degradation efficiency (Heipieper et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the energy consumption, high cost, hazardous byproducts production, and poor efficiency of these methods limited their widespread applications (Banerjee and Ghoshal, 2011). The natural ability of microorganisms to degrade phenol, and a few biological treatments of phenol are explored and found to be more efficient than physicochemical methods (Jiang et al, 2005;Banerjee and Ghoshal, 2011;Yoneda et al, 2016). It is a challenge for the wide applications of biological methods that these compounds are toxic to microbial cells, can prolong the lag phase, and reduce the phenol degradation efficiency (Heipieper et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Although recent studies found that chromatin remodeling, efflux of toxic compounds, and aggregation of lipopolysaccharides on the outer cell membrane could increase the resistance of microorganisms to phenolic aldehydes derived from lignocellulose pretreatment Yi et al, 2015), a part of the above mechanisms might be associated with the aldehyde tolerance. Another study focused on R. opacus PD630 found that phenol tolerance mainly involved the import and degradation of extracellular phenol (Yoneda et al, 2016), but the understanding of the tolerance mechanisms, not degradation mechanisms, of strains to phenol is not very clear.…”
Section: Introductionmentioning
confidence: 99%
“…Rhodococcus opacus PD630 (hereafter R. opacus) is an important microbial strain for bioproduction due to its inherently high aromatic tolerance and ability to consume many different aromatic compounds found in depolymerized lignin [19][20][21][22][23][24]. R. opacus is a Gram-positive actinomycete bacterium that can accumulate triacylglycerols (TAGs), a biodiesel precursor, up to ~ 78% of its cell dry weight when grown on sugars [25].…”
Section: Introductionmentioning
confidence: 99%
“…It also has a toxicity level that is similar to many other lignin-derived aromatic compounds [59]. In this work, phenol was chosen as a lignin depolymerization product model compound for studying changes in membrane composition that were hypothesized to be correlated with evolutionary changes that led to improved lignin depolymerization product (i.e., phenol) tolerance and utilization [20]. Increasing lignin depolymerization product tolerance in R. opacus could improve biorefinery economics by increasing product titers, yields, and productivities for lignin valorization via a hybrid conversion approach.…”
Section: Introductionmentioning
confidence: 99%
“…Since it includes both the aromatic group and phenolic hydroxyl group, phenol can effectively represent the phenolic inhibitors from lignocellulosic hydrolysis and can be used to explore the mechanisms of microorganisms' tolerance to these compounds. A previous study focused on the fermenting microorganism Rhodococcus opacus PD630 found that phenol tolerance mainly involved the import and degradation of extracellular phenol [24]. Since R.…”
mentioning
confidence: 99%